PLANNING IMPLEMENTATION OF TIME ON REPEATING PROJECT WITH LINE OF BALANCE METHOD - Cindy A. Usyor; Henry Wardhana (Universitas Lambung Mangkurat, 2017)
Some projects have cleared units of similar or exactly the same on the field. Multi - unit project is classified as very rarely activities is in many cases arise from a general breakdown of activities into specific activities. The purpose of this research to determine the time required when using heading the Line of Balance as an alternative model of the development of housing projects in Banjarmasin in terms of implementation time. At the Permata Regency Perumnas V has a repetitive activity used Line of balance. LOB is a scheduling method that is